DIGITAL TECHNOLOGIES IN THE SYSTEM OF HUMANITARIAN EDUCATION IN THE CONDITIONS OF A PHYSICAL UNIVERSITY - Batakova, N.V.; Batsina, O.N.; Tregubova, S.N. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to determine the attitude of students and teachers of a sports university to the digitalization of the educational process in the framework of the study of the humanities and natural sciences. Methods and structure of the study. To achieve this goal, a survey method was used. 125 students and 15 teachers of the Department of Social-Humanitarian, Pedagogical and Natural Sciences of the Tchaikovsky State Academy of Physical Culture and Sports took part in the survey. Results and conclusions. As a result of the experiment, the attitude and degree of adaptation of students to various forms of education during the period of quarantine measures was determined. Most of them have successfully adapted to the transition to distance learning. The attitude of students to the use of digital learning technologies in the process of studying the humanities, natural sciences is determined. The prevailing number of students "rather agree" with the use of digital learning technologies, a little more than a quarter of all students surveyed chose the category "rather disagree". Assessing the changes in the quality of education of students during the period of quarantine measures, teachers generally noted its deterioration among students of our university. Teachers consider digital technologies as progressive, allowing to diversify and intensify the educational work of students, but only as an additional tool for educational activities.